The Influence of Liquidity and Leverage on Stock Returns with Profitability as A Mediating Variable : A Study on Telecommunication Companies on the Indonesia Stock Exchange - Gede Diva Mahesa Saputra; Ni Putu Santi Suryantini (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of investors investing in stock securities is to get a high return with a certain level of risk. Return is the main factor that motivates investors to invest and as a reward for the courage to bear the risk of the investment made. This study aims to determine the influence of liquidity and leverage on stock returns with profitability as a mediating variable in Telecommunications Companies on the Indonesia Stock Exchange. This research is an associative research, by selecting telecommunication companies on the Indonesia Stock Exchange as the scope of research. The type of data in the study is secondary data obtained from www.idx.com. The sampling method used in the study used a simple random sampling method with the Slovin formula and obtained 15 telecommunications companies for the period 2020-2022. The analysis technique used in the research is descriptive analysis and path analysis. Based on the results of the analysis, it was found that liquidity has an insignificant effect on stock returns. Leverage has a negative significant effect on stock returns. Liquidity has a positive and significant effect on profitability. Leverage has a negative and significant effect on profitability. Profitability is able to mediate the effect of liquidity on stock returns and the effect of leverage on stock returns.